2017
DOI: 10.1186/s12906-017-1774-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dangguibuxue decoction on rat glomerular mesangial cells cultured under high glucose conditions

Abstract: BackgroundDysfunction of glomerular mesangial cells (GMCs) plays an important role in pathogenesis of diabetic nephropathy. Here, we investigated the effects of Dangguibuxue decoction (DBD), an herbal traditional Chinese medicinal (TCM) formula composed of Astragali Radix and Angelicae Sinensis Radix, on GMC proliferation and fibrogenesis under high-glucose (HG) conditions.MethodsSixty male Sprague Dawley rats were divided into 5 groups and administered intragastric 0.9% saline, low concentration DBD (DBD-L, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…One study manifested that it could inhibit high glucose-induced GMC proliferation and synthesis of various ECM proteins, indicating the value for treatment of DKD [85]. Other studies also showed that it could inhibit the proliferation of GMCs by attenuating the α -SMA expression and reducing hydroxyproline secretion in cultured GMCs under high glucose conditions [86].…”
Section: The Action Mechanisms Of Chm On Dkdmentioning
confidence: 99%
“…One study manifested that it could inhibit high glucose-induced GMC proliferation and synthesis of various ECM proteins, indicating the value for treatment of DKD [85]. Other studies also showed that it could inhibit the proliferation of GMCs by attenuating the α -SMA expression and reducing hydroxyproline secretion in cultured GMCs under high glucose conditions [86].…”
Section: The Action Mechanisms Of Chm On Dkdmentioning
confidence: 99%
“…It was found that the AM-AS compound could affect the concentration of TNF-α 28 , and their extracts inhibit the proliferation and fibrosis of glomerular mesangial cells (GMCs) in diabetic rats 49 . AM polysaccharides can reduce the levels of serum IL-6 and AngII in DM rats, and inhibit the expression of TGF-β1 and TNF-α 50 .…”
Section: Discussionmentioning
confidence: 93%
“…ECM protein deposition, including Collagen and Fibronectin, was related to the development of renal glomerular fibrosis in DN [29]. Besides, HG treatment induced ECM deposition, inflammation, and oxidative stress in HGMC cells, which were key pathological features of multiple renal diseases and widely reported in previous studies [30,31]. To investigate the biological role of KCNQ1OT1 in DN, HGMC cells treated with 30 mM glucose were used as the cellular model for DN.…”
Section: Discussionmentioning
confidence: 94%